EFFORTS AND LEGAL CERTAINTY IMPLEMENTATION OF ACQUIRED ASSETS (AYDA) BY THE BANK BASED ON LAW NUMBER 4 OF 1996 CONCERNING COLLATERAL RIGHTS TO LAND AND OBJECTS RELATED TO LAND - Riwenda Septiani; Gunawan Djajaputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Implementation of AYDA in the field often experiences obstacles that can cause delays in the implementation of AYDA and takes 1 (one) year to 5 more years to complete the AYDA even to the point where the process stops or gets stuck and in practice there are still many who don't follow the system set forth. regulated by UUHT. So this will cause legal uncertainty for the object of Mortgage Rights controlled by the bank so that it violates the aspect of Guarantee Law that guarantees cannot be owned by creditors. The formulation of the research problem (1) What legal steps can be taken if the implementation of the AYDA is not based on Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land? (2) What is the legal certainty of the Mortgage Object Controlled by the Bank in the Implementation of Foreclosures of More Than 1 (One) Year? The research method used is normative legal research method. The primary legal material used is the applicable laws and regulations relating to the issues to be discussed. The secondary legal materials used in this writing consist of: (1) books related to the legal issues at hand; (2) Results of research/scientific work relating to the legal issues at hand; (3) Legal magazines/journals/articles on legal issues encountered. tertiary Legal Materials, at this writing, namely: Big Indonesian Dictionary; legal dictionaries; Encyclopedia; Newspaper. The results of the study show that legal remedies that can be taken if the implementation of the AYDA are not based on Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land, namely ordinary legal remedies and extraordinary legal remedies. Legal Certainty of Mortgage Objects Controlled by Banks in the Implementation of Foreclosures of More Than 1 (One) Year, namely Mortgage Objects in principle cannot be owned by creditors as referred to in Article 12 of the Mortgage Law. To protect this principle, Article 12A of the Banking Law stipulates that collateral purchased by a bank must be resold as quickly as possible in order to pay off its receivables because banks are not allowed to own the collateral that has been purchased. This is an embodiment of legal certainty on the Mortgage object that is controlled by the bank in implementing the AYDA for more than 1 (one) year. Legal certainty in this regulation is to maintain the principle that the guarantee is not to own the goods, but is used to guarantee that the debtor will carry out his obligations until they are paid off or if they fail, they can be sold as soon as possible to pay off the debtor's debt.